Work-Family Conflict and Work Exit in Later Career Stage - Xue, Baowen (J Gerontol B Psychol Sci Soc Sci, 2020)
OBJECTIVES: This study investigated relationships between work–family conflict and routes of later-life work exit. METHODS: We used a cohort of British civil servants (5,157 men; 2,027 women) who participated in the Whitehall II study. Work interference with family (WIF) and family interference with work (FIW) were measured up to three times over 10 years. Cause-specific Cox models were used to assess the influence of WIF/FIW on particular routes (“retirement,” “health-related exit,” “unemployment,” or “homemaker/other”) of work exit in later career stage and all routes combined. RESULTS: WIF was not associated with any route of work exit in men or women, after adjusting for confounders. For perceived higher FIW, men were less likely to exit work through retirement, homemaker/other, or all routes combined. This was not attenuated by adding family factors or working conditions. Women with higher FIW were more likely to exit through the homemaker route. This was no longer significant after adjusting for family factors. Neither FIW nor WIF was associated with health-related exit or unemployment. DISCUSSION: FIW makes women more likely to become a homemaker at later career stage but reduces the risk of leaving work for men, which may reinforce gender inequality in work participation.